Epidemiology, clinical presentation, treatment, and outcome of neurosarcoidosis: A mono-centric retrospective study and literature review - Sambon, Pauline; Sellimi, Amina; Kozyreff, Alexandra; Gheysens, Olivier; Pothen, Lucie; Yildiz, Halil; van Pesch, Vincent (Frontiers in Neurology, 2022)
Introduction Neurosarcoidosis is a rare granulomatous disorder, and treatment guidelines are mainly based on retrospective studies. Materials and methods This retrospective study was performed to provide a detailed description of the clinical characteristics and treatment outcomes of patients with neurosarcoidosis followed at Cliniques Universitaires Saint Luc in Belgium. The second objective of our study was to perform a comparative literature review of neurosarcoidosis, with a focus on treatment outcomes with the use of TNF-α antagonist. Results Among 180 patients with sarcoidosis followed in our hospital, 22 patients with neurosarcoidosis were included in the final analysis. Our literature research identified 776 articles of which 35 articles met our inclusion criteria, including 1,793 patients diagnosed with neurosarcoidosis. In our cohort, the majority of patients (86%) were diagnosed with systemic sarcoidosis which was similar to that reported in the literature (83%). Serum CRP and calcemia were elevated only in 33 and 18% of patients, respectively. Serum lysozyme and angiotensin-converting enzyme were elevated in 79 and 16% of patients, respectively. Lumbar puncture and CSF fluid analysis were performed in 15/22 patients and were abnormal in all patients. Brain MRI was performed in 21/22 patients and showed abnormalities in 16 patients consisting of parenchymal lesions in 63%, hypothalamic-pituitary axis lesions in 38%, and meningeal enhancement in 31%. In both cohort patients, methotrexate was the most frequently used treatment (>45% of cases) with a favorable outcome in an average of 50% of patients. A TNF-α antagonist was administered in 9% of patients in our cohort and in 27% of patients in the literature review. The proportion of favorable outcomes in literature research was significantly higher in patients treated with TNF-α antagonists compared to methotrexate (p < 0.0001), mycophenolate mofetil (p < 0.0001), or azathioprine (p < 0.0001). Conclusion The results of our cohort and literature review confirm that neurosarcoidosis occurred most frequently in the context of systemic sarcoidosis. Methotrexate is the most frequent second-line therapy. The effectiveness of therapy with TNF-α antagonists is well-demonstrated and associated with a better outcome. Their earlier use during the disease course among aggressive and/or refractory neurosarcoidosis should be considered.